INFORMATIZATION OF THE MODERN EDUCATIONAL SPACE OF HIGHER EDUCATION FROM THE POSITION OF THE CONSCIOUS APPROACH - Aleksandrova, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The accumulated human knowledge becomes available in electronic format. Universal access to the global network is changing modern methods of teaching, education, and management. Learners are ready to use network technologies quite consciously and intuitively. The aim of the study is to identify and design the links between the development of modern society and the higher education system via information and communication technologies. The novelty of the study lies in the identification of an informative-conscious approach in the higher education system as an independent one. The study was conducted on the basis of the application of theoretical research methods. The methodological basis of the study was conceptual approach and an appeal to the origins of modern education informatization. In the field of the conducted research, aimed at the social-philosophical analysis of pedagogical activities and education, the close causality of the development of education from the development of the modern society informatization was educed. In the higher education system was individualized informative-conscious approach, that is based on the field of information and communication technologies and has the basis of an informative identity.